The dragon thief - Elliott, Zetta; B, Geneva; Elliott, Zetta (New York : Random House, 2019)
Told in two voices, Jax and Kavita, Kavita's brother Vik, and new friend Kenny try to return the baby dragon to the realm of magic before anything else goes wrong.
Sequel to: Dragons in a bag.
Horn Book, November 2019
Kirkus Review, August 2019
Resource Links, December 2019
4.0.
3-6.
Keywords: Magic -- Juvenile fiction; Dragons -- Juvenile fiction; Witches -- Juvenile fiction; Apprentices -- Juvenile fiction; Theft -- Juvenile fiction; African Americans -- Juvenile fiction; Brooklyn (New York, N.Y.) -- Juvenile fiction; Magic -- Fiction; Dragons -- Fiction; Witches -- Fiction; Apprentices -- Fiction; Stealing -- Fiction; African Americans -- Fiction; Brooklyn (New York, N.Y.) -- Fiction